Elucidating the role of Rgs2 expression in the PVN for metabolic homeostasis in mice - Yue Deng; Jacob E. Dickey; Kenji Saito; Guorui Deng; Uday Singh; Jingwei Jiang; Brandon A. Toth; Zhiyong Zhu; Leonid V. Zingman; Jon M. Resch; Justin L. Grobe; Huxing Cui (Elsevier, 2022)
Objective: RGS2 is a GTPase activating protein that modulates GPCR-Gα signaling and mice lacking RGS2 globally exhibit metabolic alterations. While RGS2 is known to be broadly expressed throughout the body including the brain, the relative contribution of brain RGS2 to metabolic homeostasis remains unknown. The purpose of this study was to characterize RGS2 expression in the paraventricular nucleus of hypothalamus (PVN) and test its role in metabolic homeostasis. Methods: We used a combination of RNAscope in situ hybridization (ISH), immunohistochemistry, and bioinformatic analyses to characterize the pattern of Rgs2 expression in the PVN. We then created mice lacking Rgs2 either prenatally or postnatally in the PVN and evaluated their metabolic consequences. Results: RNAscope ISH analysis revealed a broad but regionally enriched Rgs2 mRNA expression throughout the mouse brain, with the highest expression being observed in the PVN along with several other brain regions, such as the arcuate nucleus of hypothalamus and the dorsal raphe nucleus. Within the PVN, we found that Rgs2 is specifically enriched in CRH+ endocrine neurons and is further increased by calorie restriction. Functionally, although Sim1-Cre-mediated prenatal deletion of Rgs2 in PVN neurons had no major effects on metabolic homeostasis, AAV-mediated adult deletion of Rgs2 in the PVN led to significantly increased food intake, body weight (both fat and fat-free masses), body length, and blood glucose levels in both male and female mice. Strikingly, we found that prolonged postnatal loss of Rgs2 leads to neuronal cell death in the PVN, while rapid body weight gain in the early phase of viral-mediated PVN Rgs2 deletion is independent of PVN neuronal loss. Conclusions: Our results provide the first evidence to show that PVN Rgs2 expression is not only sensitive to metabolic challenge but also critically required for PVN endocrine neurons to function and maintain metabolic homeostasis.